2018
DOI: 10.1108/bfj-05-2017-0265
|View full text |Cite
|
Sign up to set email alerts
|

A shiitake mushroom extract as a viable alternative to NaCl for a reduction in sodium in beef burgers

Abstract: Purpose The purpose of this paper is to evaluate a shiitake mushroom extract as a potential natural taste enhancer in low-sodium beef burgers by means of sensorial and physico-chemical assays because nowadays there is a trend in the market for the development of clean-label products. Design/methodology/approach Ten formulations of beef burgers were developed, varying in the percentage reduction in NaCl (0-75 per cent) and mushroom water extracts (obtained from a 5, 12.5, or 20 per cent mushroom homogenate). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…Mattar et al. (2018) reported that the addition of different levels of mushroom extract (0%, 10%, 20%, and 30%) and reduction in NaCI (0.75%) did not have any effect on L * values of beef burgers. In another study, Cha et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mattar et al. (2018) reported that the addition of different levels of mushroom extract (0%, 10%, 20%, and 30%) and reduction in NaCI (0.75%) did not have any effect on L * values of beef burgers. In another study, Cha et al.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the growing concerns of consumers about health‐related issues, the using of additives obtained from natural sources is increasing day by day to restore their confidence instead of synthetic additives used in the meat products (Ferguson, 2010; Granato et al., 2017; Gu & Weng, 2001; Honikel, 2008; Jayaprakasha et al., 2003; Oktay et al., 2003). In many studies, the natural compounds such as various extract from plants (Hayes et al., 2010; Mathenjwa et al., 2012; Mattar et al., 2018; Schilling et al., 2019) and mushroom powders (Gençcelep, 2012; Gençcelep & Zorba, 2017; Jo et al., 2018) have been used in the formulation of emulsified meat products.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, G1S1C1 (0% mushroom, 10% fat) and G3S3C3 (30% mushroom, 20% fat) presented the lowest and highest intensity of yellow color, respectively, indicating that fat and mushroom increased the yellowness of the burger. Mattar et al (2018) and Pil-Nam et al (2015) found a higher yellow color intensity of meat products manufactured with mushroom powder in the formulation.…”
Section: Physicochemical Analysismentioning
confidence: 94%
“…Recent studies have evaluated the incorporation of mushrooms in meat-based foods aiming to reduce sodium content (Mattar et al 2018) and lipid oxidation (Tom et al 2018) and to replace fat (Wong, 2017). However, it is still unclear in which of these strategies A. bisporus presents greater potential for development of a healthier burger.…”
Section: Introductionmentioning
confidence: 99%
“…O arroz, feijão e a farinha de mandioca que foram desde o século XVIII a base do cardápio da maioria da população perderam espaço para esses produtos (DOS SANTOS, 2005). Segundo Meireles (2018) os hambúrgueres representam 13% do total das vendas de fast food no Brasil.…”
Section: Produtos Cárneos Industrializados: Hambúrguerunclassified